2015
DOI: 10.1016/j.shaw.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Shift Work and Occupational Stress in Police Officers

Abstract: BackgroundShift work has been associated with occupational stress in health providers and in those working in some industrial companies. The association is not well established in the law enforcement workforce. Our objective was to examine the association between shift work and police work-related stress.MethodsThe number of stressful events that occurred in the previous month and year was obtained using the Spielberger Police Stress Survey among 365 police officers aged 27–66 years. Work hours were derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
0
17

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 25 publications
2
84
0
17
Order By: Relevance
“…For example, working night or afternoon shifts was associated with greater total stress in police officers, even after controlling for age, sex, rank, and race/ ethnicity. 62 Shift work itself is associated with numerous poor health outcomes similar to those seen with sleep loss and circadian misalignment, such as diabetes, obesity, hypertension, impaired reproductive health, cognitive function, and cancer. 40,61,[63][64][65][66] It is likely that duration of shift work exposure, the number of night shifts worked per month, and the age at which a person started shift work also play a role in the development of poor health outcomes.…”
Section: Shift Work Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, working night or afternoon shifts was associated with greater total stress in police officers, even after controlling for age, sex, rank, and race/ ethnicity. 62 Shift work itself is associated with numerous poor health outcomes similar to those seen with sleep loss and circadian misalignment, such as diabetes, obesity, hypertension, impaired reproductive health, cognitive function, and cancer. 40,61,[63][64][65][66] It is likely that duration of shift work exposure, the number of night shifts worked per month, and the age at which a person started shift work also play a role in the development of poor health outcomes.…”
Section: Shift Work Disordermentioning
confidence: 99%
“…Maintaining regular sleep-wake times, when the work schedule allows, that permit an adequate amount of time in bed each day is important. Furthermore, because shift work may be associated with a more stressful work environment, 62 it is important to allow for an adequate time to relax before bedtime. It is also important to keep the sleeping environment cool, dark, and quiet, which can be a challenge when trying to sleep during the daytime.…”
Section: Sleep Hygienementioning
confidence: 99%
“…Nesse sentido, a própria delimitação da categoria profissional pode contribuir para suscitar a realização de outras pesquisas sobre o tema, de modo a respaldar intervenções em prol da saúde no trabalho do policial, cujas reflexões a esse respeito ainda são bastante limitantes. violência dentro e fora da corporação militar [3][4][5]8,9,21 ; trabalho em turnos 3,4,6,18 ; associação entre o estresse e as variáveis sociodemográficas 3,19,20 ; exigências do trabalho -organização do trabalho [3][4][5][6][7][8]20,21 , e discriminação de gênero 3,4,6,8 .…”
Section: Introductionunclassified
“…Essa é uma realidade muito presente no dia a dia dos policiais mais novos e/ou dos que estão há pouco tempo na corporação, que gostam do estresse e dizem que é uma das fontes de ânimo para fazer seu trabalho. Enquanto isso, os policiais com mais idade e/ou certo tempo de corporação consideram isso ruim e relacionam o estresse sofrido no trabalho aos problemas de saúde e às dificuldades de se relacionar dentro e fora do trabalho 3,8,[18][19][20] .…”
unclassified
“…Previous research into the health and wellbeing of police has identified several factors that negatively affect the psychosocial health of police and could potentially be incorporated into an occupation specific JDCS model. Those most frequently cited are shift work (27) and harassment and threats of violence (9) Shift work has been associated with a number of adverse health outcomes in a variety of professional groups, including higher levels of work stress (4,8,25), increased risk of cardiovascular disease (17,20,25), fatigue (21,(28)(29)(30)(31) and on-duty injury (3). Shift work in the police force has specifically been associated with a higher incidence of work-related stressors (27), poor sleep quality (5,32,33), increased systolic blood pressure (34) and a higher risk of workplace injury (1,35).…”
Section: Introductionmentioning
confidence: 99%